Analysis and design of single-phase power factor-corrected AC–DC Cuk converter with high-frequency isolation. (3rd January 2006) - Singh, Bhim; Agrawal, Mahima
In this paper, an analysis and design of a high-frequency transformer isolated single-phase buck-boost AC–DC Cuk converter is presented for both discontinuous and continuous conduction modes (DCM and CCM) of operation. Both modes of operation are considered for the design of 2.6-kW rating with high-level steady-state and dynamic performance. A comparative analysis of Cuk converter is also presented in both modes of operation of DCM and CCM from point of view of steady-state and dynamic behaviour, power quality, simplicity, control technique, device rating and converter size. It is observed that CCM is most suitable for higher power applications in which it requires a little complex control and sensing the additional variables.